Sugʻorish ishlarida suv ta’minotini optimallashtirish uchun noqat’iy kontroller ishlab chiqish (SCIENCE and SOCIETY, 2026)
This paper proposes a fuzzy logic-based irrigation control system for optimizing water supply in water-scarce agricultural areas of Central Asia, including Uzbekistan. The proposed system integrates five key agrometeorological parameters, namely, air temperature, soil moisture, solar radiation, wind speed, and water evaporation, into irrigation control. The proposed approach is adaptive to the environment and provides optimal irrigation control, making it suitable for use under conditions of uncertainty and variability of climatic parameters.